Removal of Methyl Violet 2B from Aqueous Solution Using Casuarina equisetifolia Needle. (8th October 2013) - Dahri, Muhammad Khairud; Kooh, Muhammad Raziq Rahimi; Lim, Linda B. L.
Abstract : One of the major contaminants of water bodies is dye pollutants that come from textile, paper, and leather industries. In this study, Casuarina equisetifolia needle (CEN) is used to remove methyl violet 2B (MV) from aqueous solutions. Batch experiments were done to investigate the contact time, effect of pH, initial dye concentrations, and temperature. Langmuir and Freundlich isotherm models were used to describe the interaction between the adsorbate and adsorbent. The sorption mechanism was described using Lagergren 1st order, pseudo 2nd order, and Weber-Morris intraparticle diffusion models. FTIR spectroscopy was used to analyze the functional groups of CEN before and after sorption with MV. Optimal conditions were found to be at room temperature with 2 h contact time and no pH adjustment was needed. Experimental data was best fitted onto Langmuir model with maximum adsorption capacity of 164.99 mg/g, while pseudo 2nd order best described the experimental data for the kinetics study. Thermodynamic parameters such as change in Gibbs free energy (Δ G 0 ), enthalpy (Δ H 0 ), and entropy (Δ S 0 ) were also investigated.